Dynamics of the Old Testament Priesthood from Aaron to Zadok - Borisov, Boris (Forum Theologicum Sardicense, 2025)
Fr. Boris Borisov (Doctoral Student at the Sofia University "St. Kliment of Ochrid) Dynamics of the Old Testament Priesthood from Aaron to Zadok The subject of this study is the distinction between the Levites, the sons of Aaron, and the sons of Zadok. The study examines various Old Testament passages that contain traces of the polemics between these rival groups. Their existence over the centuries represents competing styles within ancient Isra-elite society.